Self-reported & revealed trust: experimental evidence - Sofianos, Andis (Journal of economic psychology, 2022)
I study the relationship between self-declared trust attitudes - using a well-recognised and established personality questionnaire — and trust choices in an induced infinitely repeated trust game. I find that self-reported trust measures are significantly related with trust choices as long as trust is part of equilibrium strategies. I find that questions regarding others’ intentions is a missing component in previous work that studies self-reports of trust. An important aspect of the design is that first movers are not privy to the choices made by their partners. This design feature, coupled with an uncertainty element introduced in determining the first mover’s final payoff, allows me to analyse how first movers react to bad outcomes. Trusting individuals are more likely to give the benefit of doubt to others. Analysis of the incentivised subjective beliefs reveals that the effect of personality traits on trust choices is not through the formation of beliefs.
Gesehen am 07.04.2022
First published online: 24 October 2021